'I guess I was surprised by an app telling an adult they had to go to bed before half ten': a phenomenological exploration of behavioural 'nudges'. Issue 3 (4th May 2022) - Toner, John; Allen-Collinson, Jacquelyn; Jones, Luke
ABSTRACT: In recent years, the role of self-tracking technologies has been investigated, debated and critiqued within qualitative research circles. The principal means by which self-tracking technologies seek to promote health-related behaviours and behaviour change is through the use of 'nudges'. Despite the increasing prevalence of nudge-style modes of body-mind governance, there remains little in-depth qualitative research on people's embodied responses to this form of behavioural management. The current study sought to address this lacuna by drawing on a form of empirical, sociological phenomenology to investigate the lived experience of being 'nudged' by self-tracking technology. Our phenomenologically-inspired analysis revealed how nudges can be perceived as objectifying by rendering the user's body the intentional object of awareness. Participants agentically engaged in a sense-making process, actively (re)interpreting the relevance of nudges and assessing critically the prescribed action in the context of their everyday life. Users expressed confidence in their own embodied sensory perceptions and assessment, and resisted having their bodily intuition displaced by 'unbodied' data.